The effect of ethyl acetate fraction of Citrus limon peel on mesenchymal cell proliferation and polybacterial growth - Astrid Marinna; Priyo Hadi; Desiana Radithia (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Oral diseases remain to be global health problem. The common therapy involved the use of modern medicines with their various side effects. Citrus limon are potentials as anti-inflammatory, anti-fungal, anti-oxidant, anti-viral and anti-bacterial. Purpose: The purpose of this study was to determine the effect of ethyl acetate fraction of citrus limon peel extract on human gingival mesenchymal cell proliferation and palm commensal polybacterial growth. Method: This study was experimental study with post test only control group design. Citrus limon peel extracted and partitioned in order to obtain ethyl acetate fraction of 3.125%, 2.75%, 2.375%, 2%, and 1.5625%. Toxicity test was performed after 24 hours using the MTT Assays. Cell viability was measured by optical density formazonand read by ELISA reader 620 nm. Results: All treatment groups showed less than 60% cell viability. The highest cell was 19.36 (1.5625% concentration) and the lowest was 12.65 (3.125% concentration). The highest anti-bacterial inhibition value was 8.9125 mm (3.125% concentration) and the lowest was 6.0625 mm (1.5625% concentration). Conclusion: The higher concentration of ethyl acetate fraction Citrus limon peel extract, the higher toxicity and inhibitory properties against commensal palm polybacteria.